SAFETY MEASURES AND RISK MANAGEMENT IN CULTURAL EVENTS. A SAFE AND SECURITY MANAGEMENT APPROACH - N. MERLOI; D. NITOI; M. GHEORGHE; C. RADU; M. G. BOBOCEA (Fiabilitate şi Durabilitate)
Paper presents the current state of safety and risk management in the domain of cultural events, with an emphasis on their performance in non-conventional spaces. In this sense, the safety measures applied in the specific context of cultural events were analyzed, as well as the potential risks and dangers that can affect both the participants and the employees involved. Through the OSH (Health and Safety at Work) approach, the importance of planning and implementing effective strategies to ensure a safe and healthy environment during these events was highlighted.